MT‐102 prevents tissue wasting and improves survival in a rat model of severe cancer cachexia. Issue 2 (17th February 2020) - Pötsch, Mareike S.; Ishida, Junichi; Palus, Sandra; Tschirner, Anika; von Haehling, Stephan; Doehner, Wolfram; Anker, Stefan D.; Springer, Jochen
Abstract: Background: Cachexia, a common manifestation of malignant cancer, is associated with wasting of skeletal muscle and fat tissue. In this study, we investigated the effects of a new first in class anabolic catabolic transforming agent on skeletal muscle in a rat model of cancer cachexia. Methods: Young male Wistar Han rats were intraperitoneally inoculated with 10 8 Yoshida hepatoma AH‐130 cells and once daily treated with 0.3 mg kg −1, 3 mg kg −1 MT‐102, or placebo by gavage. Results: Three mg kg −1 d −1 MT‐102 not only prevented progressive loss of fat mass (−6 ± 2 g vs ‐12 ± 1 g; P < 0.001); lean mass (+1 ± 10 g vs. −37 ± 2 g; P < 0.001) and body weight (+1 ± 13 g vs. −60 ± 2 g; P < 0.001) were remained. Quality of life was also improved as indicated by a higher food intake 12.9 ± 3.1 g and 4.3 ± 0.5 g, 3 mg kg −1 d −1 MT‐102 vs. placebo, respectively, P < 0.001) and a higher spontaneous activity (52 369 ± 6521 counts/24 h and 29 509 ± 1775 counts/24 h, 3 mg·kg ‐1 d ‐1 MT‐102 vs. placebo, respectively, P < 0.01) on Day 11. Most importantly, survival was improved (HR = 0.29; 95% CI: 0.16–0.51, P < 0.001). The molecular mechanisms behind these effects involve reduction of overall protein degradation and activation of protein synthesis, assessed by measurement of proteasome and caspase‐6 activity or Western blot analysis, respectively. Conclusions: The present study shows that 3 mg kg −1 MT‐102 reduces catabolism, while inducing anabolism in skeletal muscle leading to an improved survival.